2021
DOI: 10.1098/rspb.2021.0671
|View full text |Cite
|
Sign up to set email alerts
|

Flexible use of a dynamic energy landscape buffers a marine predator against extreme climate variability

Abstract: Animal migrations track predictable seasonal patterns of resource availability and suitable thermal habitat. As climate change alters this ‘energy landscape’, some migratory species may struggle to adapt. We examined how climate variability influences movements, thermal habitat selection and energy intake by juvenile Pacific bluefin tuna ( Thunnus orientalis ) during seasonal foraging migrations in the California Current. We tracked 242 tuna across 15 years (2002–2016) with high-resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…The effect of this new foraging pressure on euphausiid populations, and implications for other euphausiid predators, has not yet been quantified. Large marine predators have been documented to shift their migratory patterns during warm events such as marine heatwaves, therefore changing their impact on forage species during these events (Carroll et al, 2021;Hammerschlag et al, 2022). These food web interactions are complex, and our findings support the need for greater understanding of how fluctuations in the biomass of key food web species such as euphausiids propagate upwards to higher trophic levels from a whole ecosystem perspective.…”
Section: Implications For Local Predator Populationssupporting
confidence: 57%
“…The effect of this new foraging pressure on euphausiid populations, and implications for other euphausiid predators, has not yet been quantified. Large marine predators have been documented to shift their migratory patterns during warm events such as marine heatwaves, therefore changing their impact on forage species during these events (Carroll et al, 2021;Hammerschlag et al, 2022). These food web interactions are complex, and our findings support the need for greater understanding of how fluctuations in the biomass of key food web species such as euphausiids propagate upwards to higher trophic levels from a whole ecosystem perspective.…”
Section: Implications For Local Predator Populationssupporting
confidence: 57%
“…Responses to climate change, however, vary substantially among species (Pinsky et al, 2013) and are strongly influenced by species‐specific traits (Champion et al, 2021; Sunday et al, 2015). In oceanic systems, highly mobile species may have large annual migrations brought about by their ability to follow preferential environmental conditions (Carroll et al, 2021; Fredston et al, 2021; Sunday et al, 2015). Therefore, it is important to better understand the habitat preferences of highly mobile species.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding where and to what extent suitable foraging habitat occurs throughout their range under present environmental conditions can provide insight into the sensitivity of a species to climatic shifts, whereby small geographic ranges result in higher extinction probability (Purvis et al, 2000). For example, Pacific bluefin tuna (Thunnus orientalis) employ flexible migration patterns that help compensate for energetic costs incurred from both climate change and variability in thermal oceanographic conditions (Carroll et al, 2021). Our analysis revealed that bowheads forage widely throughout the eastern Canadian Arctic, supporting earlier reports of probable foraging in nine regions across the eastern Arctic (Disko Bay, Clyde Inlet, Isabella Bay, Broughton Island, Cumberland Sound, Frobisher Bay and northern Foxe Basin) (Nielsen et al, 2015;Fortune et al, 2020c).…”
Section: Sensitivity To Climate Changementioning
confidence: 99%